2017
DOI: 10.6002/ect.2016.0065
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Our objective was to assess the accuracy of computed tomography volumetry in estimating liver volume in steatotic patients. Materials and Methods: We divided 641 liver donors (mean age 27 years, 71% male) into 4 groups ac cording to the extent of steatosis on predonation biopsy: with < 5% comprising group 1, 5% to 9% comprising group 2, 10% to 19% comprising group 3, and ≥ 20% comprising group 4. Graft mass estimation error (%) was calculated as follows: [(computed tomographymeasured volume minus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Other published methods have shown variations in accuracy. For instance, the percent error reported from using the planimetry approach was between 1% and 19% [1,2]. Manios et al [10] reported an error ranging from 5% to 9% using the random marking method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other published methods have shown variations in accuracy. For instance, the percent error reported from using the planimetry approach was between 1% and 19% [1,2]. Manios et al [10] reported an error ranging from 5% to 9% using the random marking method.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of computed tomography (CT) in the 1970s, there have been numerous methods proposed to estimate the volume of organs or tissues from CT images. The manual planimetric method of tracing the tissue's boundary is perhaps the simplest approach but has its weaknesses [1][2][3][4]: it is tedious, prone to inter-user variation, has difficulty in identifying unsharp interfaces and is often inaccurate [5][6][7]. Other, more sophisticated approaches include:…”
Section: Introductionmentioning
confidence: 99%